Construction of a Pilipino proficiency test for first year students in Eastern Leyte - Beringuel, Simplicia Tupa 1931- (1975)
The researcher constructed a proficiency test in Pilipino for first year high school students. The need to prepare linguistically sound tests for students in Eastern Leyte prompted the writer to construct a test based on the principles of second language testing. The objectives of this study are to assess the students' proficiency in Pilipino as he enters high school and to construct a reliable and linguistically valid test in Pilipino as a second language. The test proficiency aims: (1) to measure how much of Pilipino the students have mastered in order to group them for purposes of learning and (2) to find out which of the linguistic problems the students have not overcome and which they have overcome. It is also the purpose of this study to acquaint teachers with the different steps and procedures in the construction of a reliable and linguistically valid test in Pilipino as a second language.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Filipino language -- Examinations, questions, etc